THE IMPLEMENTATION OF âARIASâ STRATEGY TO INCREASE STUDENTSâ SPEAKING SKILL AT SMA NEGERI 1 BUNGORO - Sangkala, Ismail (EXPOSURE JOURNAL, 2012)
The Implementation of âARIASâ Strategy to Increase Studentsâ Speaking Skill at SMA Negeri 1 Bungoro. The objective of the research is intend to know the increasing of the studentsâ accuracy and fluency in speaking through ARIAS strategy at third year studentsâ of SMA Negeri 1 Bungoro. The method of this research is classroom action research consist of two cycles. Both of cycles consist of four meetings. It means that there are eight meetings for two cycles. The subject in this research is X.3 Senior High School in 2011-2012 academic years. That consists of 17 women and 35 men. Instruments are speaking test and observation.Keywords: Speaking, Assurance, Relevance, Interest, Assessment, Accuracy, Fluency and Satisfaction.Penerapan Strategi "ARIAS" untuk Meningkatkan Keterampilan Siswa Berbicara di SMA Negeri 1 Bungoro. Tujuan dari penelitian ini adalah ingin mengetahui peningkatan akurasi siswa dan kefasihan dalam berbicara melalui strategi ARIAS pada siswa tahun ketiga dari SMA Negeri 1 Bungoro. Metode penelitian ini adalah penelitian tindakan kelas terdiri dari dua siklus. Kedua siklus terdiri dari empat pertemuan. Ini berarti bahwa ada delapan pertemuan selama dua siklus. Subjek dalam penelitian ini adalah X.3 SMA tahun 2011-2012 tahun akademik. Yang terdiri dari 17 perempuan dan 35 laki-laki. Ada 2 intrumen yang digunakan tes berbicara dan observasi.Kata Kunci: Berbicara, Jaminan, Relevansi, Bunga, Pengkajian, Akurasi, Kefasihan dan Kepuasan.